Bangladesh Systematic Country Diagnostic, 2021 Update - World Bank (World Bank, Washington, DC, 2021)
This World Bank Group Systematic Country Diagnostic (SCD) 2021 Update presents a diagnostic of Bangladesh’s growth and poverty reduction since the previous diagnostic in 2015. It identifies emerging opportunities and challenges for the next decade as the country recovers from the COVID-19 pandemic, graduates from least-developed-country (LDC) status, and aspires to become an upper middle-income country (UMIC) by 2031. This SCD Update identifies four frontier challenges that, if tackled properly, can enable the country to accelerate its transition. This SCD Update identifies eight priorities to tackle these four frontier challenges.